Implementation of a Computer Network Security System Using the Random Port Knocking Method on the Linux Operating System at Insan Prima Mandiri Vocational School - Nurpalaha, Rifki; Zaelania, Moch Zenal; Artemysia, Khaulyca Arva; FahruRoji, Fikri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Technological advancements encourage schools to utilize computer networks for learning, making information security crucial. The purpose of this research is the implementation of a computer network security system using the random port knocking method on the linux operating system at Insan Prima Mandiri Vocational School. SMK Insan Prima Mandiri faces the risk of cyber attacks on local and wireless networks. To address this, a server security system was built using a honeypot, port knocking, and iptables. Tests were conducted before and after the system was implemented using port scanning and brute-force attacks. Results showed that before the system was implemented, the SSH (Secure Shell) port was easily accessible. After implementation, the server was able to detect and block attacks, redirect access to the honeypot, and send notifications to the admin via Telegram.